Cross‐sectional and longitudinal associations between body flexibility and sarcopenia. Issue 1 (23rd December 2022) - Gao, Peng; Gan, Da; Li, Shanshan; Kang, Qingcong; Wang, Xiaoyan; Zheng, Weifang; Xu, Xiaochen; Zhao, Xueyin; He, Wei; Wu, Joyce; Lu, Ying; Hsing, Ann W.; et al.
Abstract: Background: The associations between body flexibility and sarcopenia were not well understood. This study aimed to explore the cross‐sectional and longitudinal associations of flexibility with sarcopenia. Methods: Our study selected participants aged 50–80 from the WELL‐China cohort and the Lanxi cohort. Participants from the urban area of the Lanxi cohort were followed up 4 years later. Body flexibility was measured by the sit‐and‐reach test. Muscle mass was evaluated by dual‐energy X‐ray absorptiometry. Muscle strength was evaluated using handgrip strength. Sarcopenia was defined as having both low muscle mass and low muscle strength. We used multivariable logistic regressions to assess the cross‐sectional associations of body flexibility with low muscle mass, low muscle strength and sarcopenia. We also used multivariable logistic regressions to explore the associations of baseline flexibility and 4‐year changes in flexibility with incident low muscle mass, low muscle strength and sarcopenia. Results: A total of 9453 participants were enrolled in the cross‐sectional study, and 1233 participants were included in the longitudinal analyses. In the cross‐sectional analyses, compared with low body flexibility, high body flexibility was inversely associated with low muscle mass (odds ratio [OR], 0.58; 95% confidence interval [CI], 0.50–0.68; P  < 0.001), low muscle strength (OR, 0.62; 95% CI, 0.55–0.69; P  < 0.001) and sarcopenia (OR, 0.52; 95% CI, 0.41–0.65; P  < 0.001), and these associations did not differ in different age groups, sex or physical activity levels. In the longitudinal analyses, compared with participants with low body flexibility, participants with high body flexibility had lower risk of the incident low muscle strength (OR, 0.53; 95% CI, 0.38–0.74; P  < 0.001) and sarcopenia (OR, 0.36; 95% CI, 0.21–0.61; P  < 0.001), but not incident low muscle mass (OR, 0.59; 95% CI, 0.33–1.06; P  = 0.076). Every 1‐cm increase in flexibility during 4 years was associated with reduced risk of incident low muscle mass (OR, 0.96; 95% CI, 0.93–1.00; P  = 0.025), low muscle strength (OR, 0.96; 95% CI, 0.94–0.98; P  = 0.002) and sarcopenia (OR, 0.96; 95% CI, 0.93–0.99; P  = 0.007). Conclusions: High flexibility was associated with reduced risk of incident low muscle strength and sarcopenia. Increases in flexibility were associated with reduced risk of incident low muscle mass, low muscle strength and sarcopenia. Flexibility exercises and monitoring the dynamic change of flexibility might be helpful in preventing sarcopenia among adults aged 50 years or over.